2020 IEEE 20th Mediterranean Electrotechnical Conference ( MELECON) 2020
DOI: 10.1109/melecon48756.2020.9140570
|View full text |Cite
|
Sign up to set email alerts
|

Molecular docking of ursolic acid and Staphylococcus aureus ATPase for antibacterial therapy

Abstract: Antibiotics have transformed the practice of medicine, making once lethal infections easily treatable and making other medical advances possible. The abuse of antibiotics has contributed to the growing problem of antibiotic resistance, which has become one of the most serious and growing threats to public health. Ursolic acid is one of the most promising substances of biological origin for antimicrobial therapy. A molecular docking with Staphylococcus aureus ATPase is presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…Although the precise mechanisms underlying these findings are not known in detail, a study on the mode of action of UA against MRSA reported initial irreversible damage to bacterial membrane integrity, followed by inhibition of protein synthesis and the metabolic pathway [36]. Recently, by molecular docking, it has been hypothesized that UA can modulate the amount of ATP by inhibiting the hydrolysis of ATP (in MRSA) as polymyxins [37].…”
Section: Introductionmentioning
confidence: 99%
“…Although the precise mechanisms underlying these findings are not known in detail, a study on the mode of action of UA against MRSA reported initial irreversible damage to bacterial membrane integrity, followed by inhibition of protein synthesis and the metabolic pathway [36]. Recently, by molecular docking, it has been hypothesized that UA can modulate the amount of ATP by inhibiting the hydrolysis of ATP (in MRSA) as polymyxins [37].…”
Section: Introductionmentioning
confidence: 99%